CHARACTERISTICS OF THE SOCIETY OF THAT TIME IN THE CONTEXT OF THE PLAY MUDRARAKSHAS - Shukla, Renu; Vairagya, Vithika Das (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The play Mudrarakshasam is an extraordinary play among Sanskrit plays. This play is a heroic play based on a political story. It is not necessary to consider any play as a mere story, because through every play the playwright presents some educational topic to the audience, which becomes very important for the audience. The play Mudrarakshasam written by Vishakhadatta is no exception. Through this play, the playwright has beautifully depicted social images, through which we get a clear idea of ​​the state of society at that time. We cannot live without society because we are social beings and we learn through experience what society accepts. Just as Vishakhadatta has highlighted the social characteristics through the play Mudrarakshasam, we can learn about the social characteristics of that time through them, on the other hand, I believe that by adopting the characteristics that the society of that time finds acceptable, we can make the society more prosperous.